Interfacing Antara Peripheral Dengan Komputer Menggunakan ADC 0809 Melalui Paralel Port - Aditya Prapanca, (Teknika, 2007)
Analog to Digital Converter (ADC) representing a component which can convert an analog signal to digital form signal. Ability like this required in digital data in a measurement or analyse analog signal. While interfacing represent an equipments consisted of hardware therewith the software made as link between external world with computer. One of technique interfacing which can be done is through parallel port.In this research, designed an interfacing use ADC 0809 through parallel port which can read wide till data 4 bits. So that in this scheme needed a multiplexer, what is used to chosen upper-bits or lower-bits which step into parallel port, so that the input which only own wide of data 4 bits can accept data from ADC owning wide of data 8 bits.The result, an equipments interfacing used to measure digital tension value from output ADC (analog to digital converter, using ADC 0809) to be presented at screen of computer, by real time.